2015
DOI: 10.1007/8415_2015_185
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Load Carriage

Abstract: Study was conducted with an aim to i) study the lower limb biomechanics of healthy workers, ii) determine changes of human biomechanics with different modes of load carriage and iii) suggest biomechanically efficient mode of load carriage. Study was conducted on 20 workers in the age range 20 to 55 years. Qualisys Motion Capture System (Sweden), Kistler Force Plate (Switzerland) and Polar S810i HR monitor, Finland were used. Heart rate was recorded at rest and during different modes of load carriage with 40% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 122 publications
0
10
0
Order By: Relevance
“…Given no other study has reported changes in tibiofemoral contact forces due to armor type or load distributions (e.g., high vs. low load placement in backpacks), we cannot directly compare our results with other literature values. However, studies have shown slight variations in lower-limb joint kinematics between different load placements [ 10 , 35 ], although altered kinematics is not necessarily indicative of altered internal joint biomechanics, because muscle forces and external loads could be different. In the current study, muscle and external load contributions to total tibiofemoral contact force were the same between armor types, loads, and walking speeds ( Table 2 , S3 Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given no other study has reported changes in tibiofemoral contact forces due to armor type or load distributions (e.g., high vs. low load placement in backpacks), we cannot directly compare our results with other literature values. However, studies have shown slight variations in lower-limb joint kinematics between different load placements [ 10 , 35 ], although altered kinematics is not necessarily indicative of altered internal joint biomechanics, because muscle forces and external loads could be different. In the current study, muscle and external load contributions to total tibiofemoral contact force were the same between armor types, loads, and walking speeds ( Table 2 , S3 Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical modelling enables non-invasive characterization of external and internal biomechanical loads acting about joints, bones, and soft tissues. External biomechanical measures, such as joint kinematics and kinetics, have been reported in experimental studies of heavy load carriage during walking [ 10 , 11 ], running [ 12 ], and other military tasks [ 13 ]. However, these measures do not represent musculoskeletal tissue loads (e.g., articular contact forces and bone stresses/strains), which directly influence how tissues respond to physical training, and may more closely relate to certain MSI mechanisms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Walking is characterized by two periods during the gait cycle-the double and single support phases-when both feet are on the ground (double support) or single support where one leg is swinging through the air (swing phase). One of the main gait alterations from increased load is an increased time spent in the double support phase, a decreased length of the stride and the coinciding increase in stride frequency 31,36,38,44 . However, it is usually found that stride length and stride frequency are most altered during a fixed pace, while self-selected pacing during load carriage does not seem to have the same effect 38 .…”
Section: Spatiotemporal Changesmentioning
confidence: 99%
“…Walking with body borne loads increases peak vertical ground reaction forces (GRFs) between 5 and 10% [28][29][30][31][32][33] . The elevated GRFs are reported to increase lower limb joint and soft tissue loading 34,35 raising the risk of musculoskeletal disease 29,36,37 . To compensate for the elevated GRFs, individuals commonly exhibit significant gait spatiotemporal and joint biomechanical alterations when walking with body borne load.…”
mentioning
confidence: 99%
See 1 more Smart Citation